2016
DOI: 10.1021/jacs.5b12681
|View full text |Cite
|
Sign up to set email alerts
|

Iron Catalyzed Highly Enantioselective Epoxidation of Cyclic Aliphatic Enones with Aqueous H2O2

Abstract: An iron complex with a C 1 -symmetric tetradentate N-based ligand catalyze the asymmetric epoxidation of cyclic enones and cyclohexene ketones with aqueous hydrogen peroxide, providing the corresponding epoxides in good to excellent yields and enantioselectivities (up to 99 % yield, and 95 % ee), under mild conditions and in short reaction times. Evidence is provided that reactions involve an electrophilic oxidant, and this element is employed in performing site selective epoxidation of enones containing two a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(55 citation statements)
references
References 83 publications
0
55
0
Order By: Relevance
“…Very recently, Cussó et al. have explored C 1 ‐symmetric iron complexes containing a pdp backbone and two different heterocyclic arms . The most effective catalyst possesses a β‐TIPS‐substituted pyridine and a benzimidazole on the second arm (see ( S,S’ )‐[Fe(OTf) 2 ( Bz,TIPS pdp)] in Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Cussó et al. have explored C 1 ‐symmetric iron complexes containing a pdp backbone and two different heterocyclic arms . The most effective catalyst possesses a β‐TIPS‐substituted pyridine and a benzimidazole on the second arm (see ( S,S’ )‐[Fe(OTf) 2 ( Bz,TIPS pdp)] in Figure ).…”
Section: Resultsmentioning
confidence: 99%
“… Orthogonal regioselectivity in the asymmetric epoxidation of a dienone catalyzed by ( S,S’ )‐[Fe(OTf) 2 ( Bz,TIPS pdp)] and nucleophilic H 2 O 2 …”
Section: Resultsmentioning
confidence: 99%
“…The synthetic versatility of epoxides has established them as useful precursors to obtain a variety of polyfunctional derivatives or rearranged compounds 41, 42, 43, 44, 45, 46, 47. Cyclic α‐epoxide enones are found in a number of natural products, but asymmetric epoxidation of their precursors is notoriously difficult 48. The synthesis of β‐epoxy steroids has been achieved by using different chemical oxidants, such as chromyl diacetate, potassium permanganate salts, chiral ketones combined with oxone, and transition metal complexes in the presence of molecular oxygen 49.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Costas et al reported an iron complex with a C 1 ‐symmetric tetradentate ligand with a bulky pyridine and a benzimidazole moieties, which catalyzed the epoxidation of non‐aromatic substrates with aqueous H 2 O 2 , providing the epoxides in high yields and excellent enantioselectivities (up to 95% ee) . The experimental results also proved that the catalytic activity and stereoselectivity of an iron catalyst can be improved by enhancing the electron‐donating capacity and steric encumbrance of a ligand.…”
Section: Introductionmentioning
confidence: 94%